A qualitative exploration of thriving in elite sport - Brown, D. J.; Arnold, R.; Reid, T.; Roberts, G. (Journal of Applied Sport Psychology, 2016)
Athletes are often described as thriving in sport; however, extant research on this construct in sport has been divergent. This study aimed to provide the first dedicated exploration of thriving in elite sport performers by considering its characteristics, outcomes, and facilitators. Semistructured interviews (n = 15) were conducted with athletes, coaches, and sport psychology practitioners and were analyzed using applied thematic analysis. Thriving was perceived to comprise a sustained high-level of performance and dimensions of well-being. Furthermore, predominantly positive outcomes of thriving were described, and participants identified a network of personal and contextual enablers that could facilitate thriving.